Sticky Information vs. Sticky Prices : A Horse Race in a DSGE Framework - Mathias Trabandt (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
Mankiw and Reis (2002) have proposed sticky information as an alternative to Calvo sticky prices in order to model the conventional view that i) inflation reacts with delay and gradually to a monetary policy shock, ii) announced and credible disinflations are contractionary and iii) inflation accelerates with vigorous economic activity. We develop a fully-fledged DSGE model with sticky information and compare it to Calvo sticky prices, allowing also for dynamic inflation indexation as in Christiano, Eichenbaum and Evans (2001). We find that both models do equally well in delivering the conventional view.
urn:nbn:de:kobv:11-10050542
Keywords: E3; E0; 330; sticky information; sticky prices; inflation indexation; DSGE; Inflationsbekämpfung; Preis; Anpassung; Informationsverbreitung; Preisrigidität; Dynamisches Gleichgewicht; Stochastischer Prozess; Theorie